Republic of Lithuania : Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
The report provides the details of the IMF's projections and estimates of Lithuania on key economic and financial indicators; major privatization transactions; balance of payments; bankruptcy cases; gross domestic product by expenditure at current prices and current prices; gross value added by sector at current prices; summary of consolidated general government operations during 1998-2002; monetary authorities; deposit money banks; indicators of financial sector vulnerability; interest rates at commercial banks; average interest rates on treasury bills during 1998-2003; summary of the tax systems, July 2003, and so on.